What Determines the Efficiency of Working Capital Among Rajasthan MSMEs? - Chadha, Saurabh; Kumar Tripathi, Deepak; Tripathi, Ankita (Indian Journal of Finance, 2023)
Purpose : This research aimed to gather insights into working capital management (WCM) practices and the factors that influence its efficiency inside the Indian MSMEs’ manufacturing sector using organization variables. Methodology : For the research, the paper used panel regression methodologies on 147 MSMEs of the most critical production and manufacturing industries from 2012–2021. Findings : Several firm-specific variables, including leverage, tangibility, firm size, profitability, human capital, asset turnover ratio, and firm growth, were found to have a significant effect on working capital management efficiency (WCE); whereas, the age of the firm and salary expenses were found to have an insignificant impact on working capital management efficiency. Practical Implications : The study results will facilitate stakeholders to make informed decisions for maintaining the liquidity scenario of the MSMEs by identifying the factors most important for small businesses in Rajasthan. The state can also frame policies concerning the management of the short-term financial position of small businesses. Originality : Unlike prior research on working capital, the current work explores WCM efficiency comprehensively by including organization factors in Rajasthan manufacturing MSMEs by utilizing two efficiency metrics, that is, the cash conversion cycle (CCC) and cash conversion efficiency (CCE), which have not been studied earlier, especially in the context of Rajasthan.